Inovasi Layanan Drive Thru Dalam Upaya Meningkatkan Penerimaan Pajak Kendaraan Bermotor Pada Kantor Samsat Kota Bekasi - Mutiara Salsa Bela; Rahadi Pratomo Singgih (Jurnal Ilmu Administrasi Publik, 2022)
The motor vehicle tax is regulated in Law Number 28 of 2009 and is levied by the Regional Revenue Agency (BAPENDA). The recent research phenomenon is that a lot of people complain about the constraints of manual Samsat services as well as the lack of public awareness of paying vehicle taxes through drive-thru services. This research is aimed to analyze the innovation of Drive-Thru services to increase motor vehicle tax revenue in the Samsat Office of Kota Bekasi as well as both obstacles and efforts related to motor vehicle tax receipts through Drive Thru services. This research employed a descriptive qualitative approach. Furthermore, the theory employed is the Event M. Rogers theory of innovation with 5 indicators, namely, relative advantage, suitability, complexity, trialability, and ease of observation. The results indicated that the innovation of drive-thru service to increase motor vehicle tax revenues at the Samsat Office in Kota Bekasi of 2018 - 2020 has been well executed. This is verified by the increasing number of service users as well as the increasing number of drive-thru receipts every year. Nevertheless, the efficiency of the drive-thru service at the drive-thru outlet office in Bekasi still needs to be considered, such as service procedures that require getting off the vehicle, and the payment process that uses cash only. Meanwhile, some efforts have been executed by the Samsat Office of Kota Bekasi, namely preparing a thorough solution and evaluation so that tax revenues through the drive-thru service continue to increase and achieve the target.